2007
DOI: 10.1002/jssc.200700211
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical flow field‐flow fractionation coupled to multiangle laser light scattering detector: Optimization of crossflow rate, carrier characteristics, and injected mass in alginate separation

Abstract: The coupling of the flow field-flow fractionation (FlFFF) to differential refractive index (DRI) and multiangle laser light scattering (LS) detectors is a powerful tool for characterizing charged polysaccharides such as alginate. However, the correct interpretation of the experimental results and extrapolation of meaningful molecular parameters by using an analytical tool with such a level of complexity requires improvement of the knowledge of the alginate behavior in the channel and careful optimization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Therefore, when the carrier solution was changed from Carrier 1 to 2, pH increased from 6 to 8, leading to higher recovery and earlier elution. In addition, it has been shown that lower ionic strength would result in an increase in the electric double layer of colloids and lead to the positioning of colloids further away from the membrane [53,50,54]. Thus, this electrostatic influence may cause shorter retention time and higher recovery [36].…”
Section: Effect Of Carrier Solutions On Sample Recovery and Elution Timementioning
confidence: 97%
“…Therefore, when the carrier solution was changed from Carrier 1 to 2, pH increased from 6 to 8, leading to higher recovery and earlier elution. In addition, it has been shown that lower ionic strength would result in an increase in the electric double layer of colloids and lead to the positioning of colloids further away from the membrane [53,50,54]. Thus, this electrostatic influence may cause shorter retention time and higher recovery [36].…”
Section: Effect Of Carrier Solutions On Sample Recovery and Elution Timementioning
confidence: 97%
“…The monomers can appear in different sequences or blocks. The difficulties in analyzing alginate, due to their charged character, have been reported on in literature (Alasonati, Benincasa, & Slaveykova, 2007). Further complications may arise due to alginates, sometimes, strong viscosity enhancing effects and in a comparative study between SEC and AF4, analysis of polymers with M > 10 5 g/mol was only possible with the latter (Storz et al, 2009).…”
Section: Alginate and Carrageenanmentioning
confidence: 98%
“…Focusing and elution conditions were previously optimized by using a model EPS such as alginate (Alasonati et al, 2006(Alasonati et al, , 2007. The optimal focusing conditions used here were: focusing time t foc equal to 14 min; inlet flow rate, V in , 0.09 mL min −1 ; focus flow rate, V foc , 5 mL min −1 ; crossflow rate, V c , 4.09 mL min −1 , outlet flow rate, V out , 1 mL min −1 .…”
Section: Size and Molar Mass Distribution Of Epsmentioning
confidence: 99%